EFEITO DO TRATAMENTO COM ISOFLAVONAS DE SOJA NO EIXO OPG/RANK/RANKL (OSTEOPROTEGERINA/ RECEPTOR ATIVADOR DO FATOR NUCLEAR KAPPA B/RANK LIGANTE) EM ANIMAIS NA MENOPAUSA. - SANTOS, Fernanda Rosa Gonçalves (2019)
Introduction: Menopause is characterized by the permanent end of the menstrual periods, with a dec line in the secretion of estrogen and progesterone hormones, the physiological decrease of ovarian activity causes unfavorable changes in the metabolism of women . The molecular identification of regulators of bone resorption and formation occurs through on e of the major pathways of osteoclast differentiation and activation, and involves the RANK (RAPK) / RANK (RANK ligand) / OPG (osteoprotegerin) system. RANKL is an important molecule for the differentiation of progenitor hematopoietic cells into mature ost eoclasts and performs its effects through its binding to the RANK receptor. On the other hand, osteoclastogenesis is blocked in the presence of OPG, since when OPG is bound to RANKL, it can not bind to RANK, thus making it impossible for osteoprogenitor ce lls to differentiate into osteoclasts and there is no bone resorption. Objective: This study aims to evaluate the effects of soy isoflavones on the OPG / RANK / RANKL axis in menopausal rats. Methods: Wistar rats of the Rattus norvegicus species were used, the animals were submitted to False Surgery (SHAM) and oophorectomy (OOF), divided into 4 experimental groups: Group 1: False operated with saline solution, Group 2: Oophorectomy treated with solution saline, Group 3: Oophorectomy treated with estroproges tative (EP), Group 4: Oophorectomized treated with soy isoflavones (ISO), via gavage, for two months. Body weight, adipose tissue, uterine weight, biochemical parameters, hormonal dosage, OPG and RANKL in serum, RANKL in cerebrospinal fluid (CSF), immunohi stochemistry for immunoblotting of RANK receptors and all statistical calculations were performed using the statistical program GraphPad Prism version 6.00 for Windows. Results: The treatments did not revert the increase in body weight induced by hypoestro genism. The adipose tissue of the animals did not decrease with the treatments, it was observed that OOF (0.28 ± 0.05 g) induced atrophy of the uterus, compared to the SHAM group (0.88 ± 0.07 g). The serum calcium of the OOF group decreased (15.5 ± 2.6 ml / dL). The EP group reestablished the calcium values. Plasma magnesium levels remained the same in all groups. The levels of estradiol did not increase with the treatments, it was verified that the progesterone was reestablished in the EP and ISO groups wh en compared with the OOF group. RANKL levels in CSF, RANKL and serum OPG decreased with the treatments. The expression of RANK in the uterus increased with the treatments, in the cervix the treatment with ISO increased the expression of RANK and in the mam mary gland this expression was presented in the same way in all groups. Conclusion: It is suggested that ISOs have an effect on the regulation of the OPG / RANK / RANKL axis since treatment with this compound decreases RANKL levels in the serum of the anim als and increased the expiration of the receptor in the tissues analyzed.